Prevalence of thyroid nodules in patients undergoing thyroid ultrasonography at a tertiary care centre - Kumar Chaudhary, Arbind; Khadka, Sagar; Dulal, Sushil; Bikram Thapa, Narayan (Journal of Kathmandu Medical College, 2022)
Background: Thyroid nodules are common diseases, and have been detected up to 50% of the general population. Imaging plays a key role in the diagnosis and characterisation of thyroid diseases, and the information provided by imaging studies is essential for management planning.Objectives: To assess the prevalence of thyroid nodules in patients undergoing Thyroid ultrasonography in a tertiary care centre.Methods: A descriptive cross-sectional study was done among 86 patients. Data were collected from October 2021 to March 2022 after ethical clearance. Thyroid Imaging, Reporting and Data System were used to access the thyroid nodules. Descriptive statistics were applied using SPSS v.20.Results: The prevalence of thyroid nodules was seen in 98 (88%) individuals in total distributed in 15 (15.3%) males, and 83 (84.7%) females. Among total 98 patients, 66 (67.3%) patients had right thyroid nodules: benign 50 (51%), malignant 16 (16.3%) and 52 (53.7%) had left thyroid nodules: benign 36 (36.7%), malignant 16 (16.3%). The composition of thyroid nodules among majority participants was cystic type, anechoic type of echogenicity. Significant relationship was seen among female gender and malignancy, solid composition of thyroid nodules, and ill-defined margin.Conclusion: The prevalence of thyroid nodules was higher in comparison to other studies. Sonographic features like consistency, margin, and echotexture could differentiate benign and malignant thyroid nodules by using Thyroid Imaging Reporting and Data System.